Correlation between Flotation and Rheology of Fine Particle Suspensions - Sajjad, Mohsin; Otsuki, Akira (Metals (Basel ), 2022)
This paper summarizes and discusses previous investigations into the correlation between the rheology and flotation process of fine particle suspensions. This summary provides a better understanding of the challenges and current status of this subject and useful feedback based on the revision of relevant theories and practical implications for fine particle characterization and processing. Such processes include the sustainable beneficiation of complex ores and wastes for valuable material extraction and the segregation of toxic substances. For example, there has been increasing demand for the beneficiation of complex ores often carrying the values (e.g., critical raw materials) in fine grains, due to the noticeable decrease in the accessibility of high-grade and easily extractable ores. To maintain the sustainable use of limited resources, the effective beneficiation of complex ores is urgently required. It can be successfully achieved only with selective particle/mineral dispersion/liberation and the assistance of mineralogical and fine particle characterization including a proper understanding of the rheological behavior of complex ores in the context of fine particle separation/processing. In correlating flotation with suspension rheology, previous works were summarized and we found that the modeling of their correlations as well as comprehensive contributions of pulp and froth rheology on flotation performance have been studied very limitedly, and comprehensive developments in these aspects are thus strongly suggested.